Review on Social Aspects Activity In the Sustainability Report (Study on Bank Mandiri and BCA) - Wijaya, Aida; Wijaya, Aida (CENTRAL ASIA AND THE CAUCASUS, 2022)
This research aimed to review the banks’ readiness to comply with the social aspects regulated in the Financial Service Authority Regulation (POJK) No. 51/POJK.03/2017. The object of the study was the sustainability reports issued by two biggest banks in Indonesia, one was BCA – a non-State-Owned bank, and the other was Bank Mandiri – a State-Owned bank. The findings showed that both stated-owned and non-state-owned banks had implemented the activities as indicated in the regulations quite well. They even mentioned their commitment to support the Sustainable Development Goals.